Sytuacja finansowa przedsiębiorstw mleczarskich w Polsce w latach 1994-1998 - Pietrzak, Michał (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
The paper examines financial performance of enterprises operating in dairy sector over the 1994-1998 period. During the five years under consideration, significant changes have occurred both in the average size and structure of the assets and liabilities. Along with an average increase in assets, the portion of working assets and current liabilities in total assets and liabilities has risen. lt was observed that average annual dynamics of the sector's turnover was higher in comparison with the inflation rate but costs were growing faster than revenues. It is also worth to point out that the most rapid growth in the assets and turnover was noted in the case of the largest dairy enterprises. Among the balance sheet 1 and financial statement analysis, indicators of Among the balance sheet and financial statement analysis, indicators of dairy business profitability and performance were analysed. The following were taken into consideration: liquidity ratio, debt ratio and profitability ratio. The study results indicate that the most dairies faced liquidity ratios at the level slightly below the optimal one. Furthermore, the rise in the level of debt ratios was observed and surprisingly the rising portion of expensive short-term credits in assets financing. An average profitability of the sector was around zero. The lowest profitability was noticed in 1998, when 60 per cent of dairies generated losses. Referring to Porter's statement that average profitability reflects competitiveness of the sector, one can say that the dairy industry in this respect is in unfavourable position.